Hubungan Ukuran Lingkar Pinggang terhadap Kadar Asam Urat pada Pria dengan Pekerjaan Aktivitas Fisik Rendah - Irfan Darfika Lubis; Rahmanda Artamevia; Eka Febriyanti; Yuanita Mayasari Aritonang (Pusat riset dan Inovasi Nasional, 2026)
Background: Hyperuricemia represents a medical condition marked by elevated concentrations of uric acid within the bloodstream, potentially triggering gout alongside various metabolic disorders. Central obesity has been identified as a contributing factor to rising uric acid concentrations, measurable through waist circumference assessment. Methods: An analytic observational design utilizing a cross-sectional approach was employed in this investigation, encompassing 100 male participants characterized by sedentary lifestyles who were employed as office workers in Medan City, North Sumatra Province. Waist circumference measurements were obtained using a flexible measuring tape, while uric acid concentrations were determined through Point of Care Test (POCT) devices. Statistical evaluation was conducted via the Chi-Square test, applying a significance threshold of 0.05. Results: Among all participants, 64 individuals (64%) exhibited waist circumference measurements indicative of central obesity, whereas 56 individuals (56%) demonstrated hyperuricemic conditions. Statistical evaluation revealed a significant association between waist circumference measurements and uric acid concentrations, evidenced by a p-value of 0.000 (p < 0.05). Conclusion: A meaningful correlation exists between waist circumference and uric acid concentrations among males engaged in sedentary occupations.